Clinical and Microbiological Profile of Bacterial Keratitis in Indonesia: A Retrospective Study at a National Eye Center - Hanifa, Nadhira Nizza; Idrus, Elfa Ali; Kartika, Antonia (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2025)
Introduction: Bacterial keratitis, accounting for 90% of microbial keratitis cases globally, poses a serious threat to vision and is a leading cause of corneal blindness globally. This study provides novel insight and integrated analysis of bacterial keratitis at the National Eye Center, providing epidemiological insight in a tertiary eye center, which has not been previously reported in published literature to guide effective clinical decision making and public health strategies. Methods: This descriptive retrospective study was done at the National Eye Center. Data on demographics, presenting signs and symptoms, bacteriological examination results, treatment administered, and complications observed were collected from medical records between January to December 2023. Result: Among 33 patients, 51.5% were female with a mean age of 41.6 years. The majority (81.8%) had predisposing factors, with corneal trauma (48.5%) being the most common. Microbiological analysis by corneal scraping revealed gram-positive cocci in 72.7% of cases. Most patients (78.8%) were managed with topical antibiotics alone. Surgical intervention was required in 21.2% of cases due to complications. Conclusion: The findings highlight corneal trauma as the leading risk factor, predominantly gram-positive cocci involvement, and the necessity of timely intervention to prevent complications. Further large-scale studies are needed to refine management strategies.